The postoperative analgesic efficacy of different regional anesthesia techniques in breast cancer surgery: A network meta-analysis - An, Ran; Wang, Dan; Liang, Xiao-Long; Chen, Qi; Pang, Qian-Yun; Liu, Hong Liang (Frontiers in Oncology, 2023)
Background Regional anesthesia have been successfully performed for pain management in breast cancer surgery, but it is unclear which is the best regional anesthesia technique. The aim of the present network meta-analysis was to assess the analgesic efficacy and disadvantages of regional anesthesia techniques. Methods Multiple databases were searched for randomized controlled trials (RCTs). The association between regional anesthesia and analgesic efficacy was evaluated by Bayesian network meta-analysis. Results We included 100 RCTs and 6639 patients in this study. The network meta-analysis showed that paravertebral nerve block, pectoral nerve-2 block, serratus anterior plane block, erector spinae plane block, rhomboid intercostal block, and local anesthetic infusion were associated with significantly decreased postoperative pain scores, morphine consumption and incidence of postoperative nausea and vomiting compared with no block. Regarding the incidence of chronic pain, no significance was detected between the different regional anesthesia techniques. In the cumulative ranking curve analysis, the rank of the rhomboid intercostal block was the for postoperative care unit pain scores, postoperative 24-hour morphine consumption, and incidence of postoperative nausea and vomiting. Conclusion Regional anesthesia techniques including, paravertebral nerve block, pectoral nerve-2 block, serratus anterior plane block, erector spinae plane block, rhomboid intercostal block, and local anesthetic infusion, can effectively alleviate postoperative acute analgesia and reduce postoperative morphine consumption, but cannot reduce chronic pain after breast surgery. The rhomboid intercostal block might be the optimal technique for postoperative analgesia in breast cancer surgery, but the strength of the evidence was very low. Systematic review registration https://www.crd.york.ac.uk/prospero/(PROSPERO), identifier CRD 42020220763.